Quaternary Geology of the Itasca - St. Croix Moraine Interlobate Area, North-Central Minnesota - Norton, Arthur Randolph (1982)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Arthur Randolph Norton in partial fulfillment of the requirements for the degree of Master of Science, December 1982. Plates I-III referenced in the thesis are also attached to this record. Please note that Plates II and III are mislabeled on the actual plates; the file names contain the correct plate numbers, as determined by matching the plate titles on the plates to the plate titles listed in the thesis. During the St. Croix Phase of the Late Wisconsinan Substage, two lobes of the Laurentide Ice Sheet terminated and formed an interlobate junction in Cass County, Minnesota. Coarse textured, yellowish- to reddish-brown supraglacial sediments (Brainerd Till) were deposited as the north-south trending St. Croix Moraine by a southwestward advance of the Brainerd Sublobe of the Rainy Lobe. Brainerd Till is characterized by a high percentage of reddish crystalline rocks derived from a source area to the northeast and also by a low percentage of carbonate, probably derived by incorporation of underlying carbonateÂ·-rich till. The terminal position of the Brainerd .Sublobe is also marked by a continuous fosse and dump ridge at the head of the westerly grading Oshawa outwash plain. A second outwash plain was formed behind the St. Croix Moraine during retreat of the Rainy Lobe at the end of the Itasca-St. Croix Phase. A contemporaneous advance of the Wadena Lobe deposited the Lower Red Lake Falls Formation, a light olive brown to gray sandy loam till which contains moderate amounts of carbonate clasts and sparse northeast-source rock types. The bulk of the sediments were deposited as the east-west trending Itasca Moraine. Within that moraine are numerous sets of transverse compressional ridges with a broad curvature to the northeast, reflecting a south-southwesterly course for the Wadena Lobe at its terminus. An advance of that glacier to a position some 25 km south of the Itasca Moraine is indicated by extra-moranic ti11 and ...